Геохимическая зональность Бетюгенского золотосурьмяного рудного поля (Республика Саха (Якутия)) - Гаврилов Р. Ю. Роман Юрьевич; Ворошилов В. Г. Валерий Гаврилович; Сенкевич В. С.; Тямисов Н. Э.; Широков В. В. (2015, 2015)
Заглавие с экрана